2017
DOI: 10.32831/jik.v3i2.54
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Ibu Tentang Gizi Dengan Status Gizi Balita Usia 1-5 Tahun Di Desa Kedawung Wilayah Kerja Puskesmas Ngadi

Abstract: One of the factors that affect the nutritional status of children is the mother's knowledge. Knowledge is a determinant of attitudes and behavior of the mother. Knowledge required for the application of the provision of food for the nutritional needs so that the nutritional status of children is known. The purpose of this study was analyze the correlation between nutrition knowledge of mothers about nutrition with nutritional status of children aged 1-5 years in Kedawung Village Ngadi health center. The resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…with the highest nutritional status of children, namely poor nutritional status as many as 52 respondents (53.06%) (Rika, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…with the highest nutritional status of children, namely poor nutritional status as many as 52 respondents (53.06%) (Rika, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…17 Based on the results of research conducted in Sawah Lebar Health Center Bengkulu 2023, stunting was found to be more stunted children with poor maternal knowledge of nutrition (54.5%), this condition occurs because maternal knowledge of nutrition directly affects nutritional intake in children and mothers do not know the kinds of nutrients and food ingredients. According to Titisari et al 25 the lack of knowledge of mothers about nutrition can make the mother's behavior in paying attention to the nutrition of her toddler less than optimal. The majority of respondents who are less knowledgeable and have toddlers with undernourished status, they are not good at preparing menus for their toddlers.…”
Section: Discussion Of Nutritional Knowledge Of Mother With the Incid...mentioning
confidence: 99%
“…Apabila kekurangan gizi ini berlanjut dan semakin berat, akan menghambat pertumbuhan balita dan membuatnya lebih kecil. Kekurangan gizi ini juga dapat menyebabkan keterlambatan dalam perkembangan motorik yang meningkat, perkembangan emosi dan tingkah laku (Titisari et al, 2017).…”
Section: Pendahuluanunclassified